Literasi Industri Halal dan Intensi Berkarier Mahasiswa Muslim Generasi Z di Sektor Halal Kota Serang - Luthfi Ardhiona; Moh. Mukhsin (Yayasan Penelitian dan Pengabdian Masyarakat Sisi indonesia, 2026)
The rapid growth of the halal industry in Indonesia has created broader career opportunities for young Muslims. However, studies examining the relationship between halal industry literacy and career intention in the halal sector remain limited. This study aims to explore halal industry literacy and career intentions among Muslim Generation Z students toward the halal sector. A descriptive qualitative approach was employed using purposive sampling. The participants consisted of 14 Muslim Generation Z students in Serang City from various academic disciplines. Data were collected through in-depth interviews and analyzed using descriptive qualitative techniques. The findings indicate that students’ halal industry literacy remains at a basic level, focusing primarily on halal products rather than understanding the halal industry as an integrated economic ecosystem. Meanwhile, career intention in the halal sector is categorized as potential, as students generally express interest in the sector but lack clear career planning. The study further suggests that a better understanding of the halal industry tends to be associated with stronger interest in pursuing careers within the halal sector. In addition, career information, motivation, and social environment were found to contribute to students’ career intentions.